Economic evaluation of sterilization reversal in infertility treatment: A systematic review - Brandon Chongthanadon; Suvijak Untaaveesup; Chayanis Kositamongkol; Pochamana Phisalprapa; Krasean Panyakhamlerd; Vitaya Titapant (PLoS ONE, 2026)
Objectives Although sterilization is intended to be permanent, some individuals later seek fertility. In such cases, options can be limited and financially burdensome. This review evaluated the cost-effectiveness of sterilization reversal surgery in previously sterilized individuals. Methods We searched MEDLINE, Embase, and Scopus from inception in 1946 through December 2025, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidance. We included studies that analyzed cost-effectiveness or reported the costs of sterilization reversal in males (vasectomy reversal) or females (tubal anastomosis), with assisted reproductive technologies as comparators. Study quality was assessed using the Consolidated Health Economic Evaluation Reporting Standards 2022 checklist. Two authors independently screened each study to reduce bias. All costs per outcome were converted to 2024 United States dollars for analysis and comparisons. Results Of 1628 identified articles, 24 studies met the eligibility criteria. Almost all examined populations in high-income countries, such as the United States, the Netherlands, and Singapore. Thirteen studies evaluated tubal anastomosis, and eleven evaluated vasectomy reversal. Most studies reported lower total costs for sterilization reversal than for assisted reproductive technologies, with comparable outcomes. Vasectomy reversal was preferred for male patients irrespective of the female partner’s age, whereas tubal anastomosis was preferred for female patients aged 40 years or younger. For older patients, assisted reproductive technologies were more cost-effective. Conclusions Tubal anastomosis and vasectomy reversal may be economically advantageous compared with assisted reproductive technologies for infertility due to prior sterilization. However, societal factors, including a country’s socioeconomic context and policy feasibility, should be considered.